GENDER DIFFERENCES IN REPRODUCTIVE HEALTH RISKS, HEALTH CARE SEEKING BEHAVIOR, AND PSYCHOLOGICAL DISTRESS AMONG ADOLESCENTS - Roichatul Djannah (International Journal of Multidisciplinary Research and Literature, 2025)
Adolescent reproductive health is an important aspect of physical, psychological, and social development. Biological changes in adolescence can give rise to a variety of different reproductive health complaints between males and females. This condition has the potential to be related to psychological distress, especially if adolescents experience worries, discomfort, or limited access to information and health services. This study aims to analyze the differences in reproductive health risks and psychological distress between adolescent boys and girls. The study used a quantitative design with a cross-sectional approach. The research sample amounted to 198 adolescents, consisting of 72 adolescent boys and 126 adolescent girls. Reproductive health variables were measured through the components of C1 general conditions, C2 specific men, C3 specific women, C4 health care behaviors, and total reproductive health risks. Psychological distress was measured using the K10 adaptation instrument. Bivariate analysis was performed using Chi-Square, Mann-Whitney, and Spearman correlation tests. The results showed that there was a significant difference in reproductive health risks based on sex with a p value of < 0.001. Adolescent girls are more in the category of moderate reproductive health risk than boys. Psychological distress was also significantly different between males and females with a p< value of 0.001. Adolescent girls show a higher proportion of severe distress than boys. Total reproductive health scores and distress scores were also higher in adolescent girls. These findings point to the need for gender-sensitive reproductive health and mental health interventions in school settings.